1999
DOI: 10.1029/99eo00412
|View full text |Cite
|
Sign up to set email alerts
|

Analysis links Pacific decadal variability to drought and streamflow in United States

Abstract: The two leading patterns of Pacific decadal sea surface temperature (SST) variability are strongly linked to large‐scale patterns of warm‐season drought and streamflow in the United States, recent analysis shows. The predictive potential of this link may contribute to the development of warm‐season hydroclimate forecasts in the United States. Understanding of low‐frequency variations in drought and streamflow would be important for both agriculture and water resources management. The two leading patterns are w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(77 citation statements)
references
References 9 publications
1
76
0
Order By: Relevance
“…The correlation between these patterns is 0.92. The PDO has been shown previously to modulate winter precipitation in the U.S. (12)(13)(14), as well as summer drought and streamflow in the conterminous U.S. (15).…”
Section: Resultsmentioning
confidence: 99%
“…The correlation between these patterns is 0.92. The PDO has been shown previously to modulate winter precipitation in the U.S. (12)(13)(14), as well as summer drought and streamflow in the conterminous U.S. (15).…”
Section: Resultsmentioning
confidence: 99%
“…Some previous studies (Latif and Barnett, 1996;Mantua et al, 1997;Cayan et al, 1998;Nigam et al, 1999;Higgins and Shi, 2000;Minobe, 2000;Neal et al, 2002;Krishnan and Sugi, 2003;Wang et al, 2008) have indicated that the interannual relationship between ENSO and global climate is not stationary and that the Pacific Decadal Oscillation (PDO), which is a largely interdecadal oscillation, can modulate the interannual ENSO-related teleconnections. For instance, the already enhanced precipitation and streamflow in eastern Australia have been demonstrated to be even further magnified during La Niña events that occurred in the PDO/IPO (Interdecadal Pacific Oscillation) cool phase (Verdon et al, 2004).…”
Section: R Ouyang Et Al: Linkages Between Enso/pdo Signals and Precmentioning
confidence: 99%
“…This change in the North Pacific climate may be 20 1900 1910 1920 1930 1940 1950 1960 1970 1980 1990 1900 1910 1920 1930 1940 1950 1960 1970 1980 1990 another driving force behind the recent warming trend in the Great Lakes region. Links between the PDO and North American circulation, precipitation, and temperature anomalies are becoming the subject of intense research (Latif & Barnett 1996, Nigam et al 1999, Hare & Mantua 2000, Barlow et al 2001. Deser & Blackmon (1995) have linked the SST decadal variability in the North Pacific to the Pacific North American (PNA) atmospheric circulation pattern, which substantially impacts US winter weather (e.g.…”
Section: Abstract: Great Lakes · Pacific Decadal Oscillation · El Nimentioning
confidence: 99%